Brand name bullies : - Bollier, David (John Wiley & Sons, 2005)
Imagine if today's far-reaching laws on copyright and trademark were sent back in time to the days of William Shakespeare. On the opening day of Romeo and Juliet, the heirs of first-century Roman poet Ovid would surely have filed the case of Estate of Ovid v. William Shakespeare, alleging that the Bard had made unauthorized use of Ovid's Metamorphoses, which is also based on two lovers from warring families. The legal conflict would have scared off theaters, and the play would have dropped into obscurity. It might seem ridiculous, but David Bollier, author of Brand Name Bullies, says this scenario is common under today's copyright and trademark law, which he calls "replete with tales of the bizarre and hilarious."